Pembiaran Pada Potensi Konflik dan Kontestasi Semu Pemilukada Kota Blitar: Analisis Institusionalisme Pilihan Rasional - Ramadlan, Moh. Fajar Shodiq; Wahyudi, Tri Hendra (Jurnal Politik Indonesia: Indonesian Political Science Review, 2016)
The simultaneous local election is the new step of democratization in Indonesia. Viewing an implementation about the local election in each district which have many of potential conflict and unrest, conflict managements required to anticipate a potential conflict. This paper will suggest to describe about conflict management of the local election in Blitar City using an rational choice institutionalism approach, assuming that institutions has a capacity to solve a problem of conflict management in the local election. Blitar city been selected because it has a particular aspect that the two candidates, namely by incumbent and independent, but the contestation is pseudo-contestation. This paper is the result of exploratory qualitative research. The techniques to explore data is use focus group discussion that involved an institutions related with Blitar local election. Belong this research, the institutions that related in the local elections understand a potential conflict, but the selected conflict management is avoiding method.